Preparation and properties of paraffin/SiO2 composite phase change materials - ZHONG Li-min; YANG Mu; LUAN Yi; ZHANG Xiao-wei; GAO Hong-yi; FENG Yan-hui; FENG Dai-li (工程科学学报, 2015)
Paraffin/SiO2 composite phase change materials based on a paraffin core and a silica shell were prepared using TEOS as a silica source through a sol-gel method under acidic condition. Fourier transformation infrared spectroscopy,X-ray diffraction,scanning electron microscopy,differential scanning calorimetry and thermogravimetry were employed to investigate the morphology,chemical structure,crystalloid phase,phase change properties and thermal stability of the composite materials. The results show that the paraffin/SiO2 materials have core/shell morphology with a diameter of about 2 μm. When the core/shell mass ratio reaches 2:1,the encapsulated ratio of paraffin is 66.3%,the melting point of the composites is 54.2℃ with a latent heat of 133.8 J·g-1,and the solidifying temperature is 49.5℃ with a latent heat of 127.5 J·g-1. In comparison to traditional composite phase change materials with a polymeric shell,the thermal conductivity of the paraffin/SiO2 materials increases due to the extra silica shell. This advantage expands applications in building materials and textile fabrics.